Visceral sensitivity modulation by faecal microbiota transplantation: the active role of gut bacteria in pain persistence. Issue 5 (13th May 2022) - Lucarini, Elena; Di Pilato, Vincenzo; Parisio, Carmen; Micheli, Laura; Toti, Alessandra; Pacini, Alessandra; Bartolucci, Gianluca; Baldi, Simone; Niccolai, Elena; Amedei, Amedeo; Rossolini, Gian Maria; Nicoletti, Claudio; et al.
Abstract : Supplemental Digital Content is Available in the Text. Persistent visceral pain induced by colitis in rats can be either transferred to controls or counteracted by mean of a faecal microbiota transplant. Abstract: Recent findings linked gastrointestinal disorders characterized by abdominal pain to gut microbiota composition. The present work aimed to evaluate the power of gut microbiota as a visceral pain modulator and, consequently, the relevance of its manipulation as a therapeutic option in reversing postinflammatory visceral pain persistence. Colitis was induced in mice by intrarectally injecting 2, 4-dinitrobenzenesulfonic acid (DNBS). The effect of faecal microbiota transplantation from viscerally hypersensitive DNBS-treated and naive donors was evaluated in control rats after an antibiotic-mediated microbiota depletion. Faecal microbiota transplantation from DNBS donors induced a long-lasting visceral hypersensitivity in control rats. Pain threshold trend correlated with major modifications in the composition of gut microbiota and short chain fatty acids. By contrast, no significant alterations of colon histology, permeability, and monoamines levels were detected. Finally, by manipulating the gut microbiota of DNBS-treated animals, a counteraction of persistent visceral pain was achieved. The present results provide novel insights into the relationship between intestinal microbiota and visceral hypersensitivity, highlighting the therapeutic potential of microbiota-targeted interventions.